The Impact of Wages and Unemployment on Youth Enrollment and Labor Supply - Gustman, Alan L.; Steinmeier, Thomas L. (The Review of Economics and Statistics, 1981)
Various aspects of the school enrollment-labor supply decision have been examined in earlier studies, including those of Bowen and Finegan (1969), Cohen, Rea, and Lerman (1970), Duncan (1965), Katz (1973), Korbel (1966) and Lerman (1972). Although these authors were aware of the joint nature of the school-work decision, typically, they used an ordinary least squares (OLS) framework with dichotomous dependent variables to analyze enrollment conditional on the labor supply decision or labor supply conditional on enrollment. Several more recent studies, such as Antos and Mellow (1978), Stephenson (1978), and Ehrenberg and Marcus (forthcoming) use multinomial logit to analyze the joint determination of labor supply and enrollment. Mallar (1976) uses a bivariate probit model to deal with the simultaneous relation between school and work. But none of these studies considers both the wage offers and job availability. There is still available no single set of estimates which considers the roles of both job availability and the wage on the joint enrollment-labor supply decision. Consider what the interrelation between wages and job availability implies for estimation of the labor force participation-school enrollment decision. To the extent that downwardly rigid wages prevent the youth labor market from clearing, one would expect both wages and job availability to influence labor supply. If one of these measures is not included in explaining labor supply, the coefficient estimated for the other measure may, for reasons well known, be biased. For example, if the wage is omitted but the unemployment variable included, and if wages and unemployment are negatively correlated, then the magnitude of the coefficient of the unemployment variable will be increased. It is also unclear on a priori grounds how job availability affects school enrollment. On the one hand, if jobs are readily available to young people, youth from poor families may be able to enroll in school, supporting themselves through part-time work. With no jobs available, some may be unable to afford school expenditures and may drop out (Bowen and Finegan, 1969, p. 404). On the other hand, readily available employment opportunities for youth may simply raise the probability of dropping out of school and working full-time. Our findings will help to determine how young people react to this influence and to other influences of the market. From the viewpoint of public policy, there are a number of reasons why it is important that the enrollment-labor supply decisions be understood, and that the separate responses to wage and job availability be isolated. For one thing, there is a tendency to discount the welfare importance of unemployment or poor labor participation for young people enrolled in school (Feldstein and Ellwood, 1979). However, the joint nature of the enrollment-labor supply decisions suggests that a high enrollment rate may not be simply a cause of low participation rates, but may be an additional symptom of adverse labor market conditions. Indeed, our results for nonwhite males support an interpretation of this kind. Second, the joint nature of the decisions also implies that public programs such as the Received for publication January 31, 1980. Revision accepted for publication December 11, 1980. * Both authors are with Dartmouth College and the National Bureau of Economic Research. The research reported here was supported by the Division of Technical Systems in the Office of Technical and Analytic Systems, Office of the Assistant Secretary for Planning and Budget, U.S. Department of Education and is part of the NBER's research program in Labor Studies. Any opinions expressed are those of the authors and not those of the National Bureau of Economic Research or of the Department of Education. We would like to thank Gary Fields, Meir Kohn, Robert Plotnick, Martin Segal and participants in the labor seminars at Harvard and at Cornell for their helpful comments.